A CLIENT WITH SPECIAL NEEDS IN TOURIST SERVICES - NOVIKOVA, Nataliya Gennadievna; KORTUNOV, Vadim Vadimovich; KRASNOVA, Olga Nikolaevna; ZORINA, Natalia Mikhailovna; KIREENKOVA, Zoya Alexandrovna (Journal of Environmental Management and Tourism, 2016)
Tourism plays a significant social and cultural role in contemporary society by developing new behavior algorithms of various society categories. Tourist flow expands, as well as the number of people with limited abilities, who, while remaining handicapped due to multiple social obstacles, are in need of adaptive conditions for consuming tourist services inside the tourism, available for everyone. Including disabled people in the tourism area still remains an unsolved problem. People with special needs in tourist services are considered being excluded from the social life. Questions related to offering tourist services to them are being solved only partially; there are no conditions for such activity. There is hardly any information about the opportunities for people with limited abilities in Russian; and the least available and the least studied is the field of using tourism facilities in the system of means of social protection. At the same time, tourists with special needs in tourist services are potential business clients; they can participate in economic development and provide profit. We suppose that, to certain extent, this is related to insufficient development of theoretical and conceptual problems of adaptive tourism, which particularly affects the issues of society’s attitude towards such concepts as “human health” and “disability”. Viewing adaptive tourism as a system of social, psychological, medical, athletic, recreational and other interactions, which are included in the content of tourist activity while providing tourist services to the people with special needs, the priority is set on a certain type of psychosocial work on all levels of tourist industry. Adaptive tourism aims on studying and realization of subject-subject interactions, which accompany the promotion of tourism products to the people with special needs. And this implies not only elimination of mechanic obstacles for the travelers’ transportation. There is an issue of a specific type of work with people, who have special needs in tourist services. Lack of attention towards the social category, which needs special conditions in tourism, and under-development of required infrastructure lower the motivation for gaining knowledge in those, who would like to provide specific tourist services for people with limited capabilities in their professional activity. Adaptive tourism is based, on the one hand, on the general theory and methodology of social work, and on the other hand, on the technology of organizing tourism activity and the concept of adaptive physical culture (adaptive physical education, adaptive sport and adaptive locomotor recreation). Our study allows developing a scientific and theoretic basis of the conceptual model of special tourism activity and suggesting a profile for teaching psychosocial workers, who are capable of organizational and managerial activity with people, who have special needs in tourist services.
Keywords: disability; lifestyle limitations; special needs; tourist services; adaptive tourism